2014
DOI: 10.2478/pjvs-2014-0057
|View full text |Cite
|
Sign up to set email alerts
|

Chicken intestinal microbiota function with a special emphasis on the role of probiotic bacteria

Abstract: Bacterial colonization of the chicken gut by environmental microbes begins immediately after hatching. Composition of the intestinal microbiota is dependent on the surrounding environment, diet variation, pathological conditions, antibiotic therapy, and others. The genomes of all these intestinal microbes form a microbiome which by far outnumbers the host's genome. As a consequence, the microbiome provides additional metabolic functions to the host, including nutrient utilization and absorption, fermentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 69 publications
2
62
1
2
Order By: Relevance
“…Furthermore, we detected greater ileal villi size in the F 4 group. This is closely related to tissue turnover in the crypt region and could be induced, before bacterin immunization, through different bioactive molecules after the interaction between epithelial cells, microbiota, and immunological cells, to conserve mucosal homeostasis (11, 13, 14, 34, 35). Moreover, this increased number of lymphocytes inside the lamina propria of the ileum villi in the F 4 group was consistent with the increased number of plasmatic cells registered between epithelial cells near the top of the villi (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we detected greater ileal villi size in the F 4 group. This is closely related to tissue turnover in the crypt region and could be induced, before bacterin immunization, through different bioactive molecules after the interaction between epithelial cells, microbiota, and immunological cells, to conserve mucosal homeostasis (11, 13, 14, 34, 35). Moreover, this increased number of lymphocytes inside the lamina propria of the ileum villi in the F 4 group was consistent with the increased number of plasmatic cells registered between epithelial cells near the top of the villi (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…i Clostridium difficile (41). Do listy przeciwbakteryjnych produktów jelitowej mikrobiota i bakterii probiotycznych należy również dodać utleniający czynnik, jakim jest H 2 O 2 , niewrażliwe na ogrzewanie i proteazy substancje bakteriocynopodobne i inne bliżej nieokreślone substancje (9,17).…”
Section: Kompetycyjne Wykluczanieunclassified
“…Campylobacteriosis is the most commonly reported zoonosis (EFSA 2015). To reduce human infections with Campylobacters, it is necessary to reduce the colonization in the chickens (Cisek and Binek 2014). Modern broiler rearing has taken attention to natural substances which can help them maintain healthy status of fowls.…”
Section: Doi: 1017221/12/2017-cjasmentioning
confidence: 99%
“…Therefore, farmers, breeders have been looking for probiotic microbiota. In poultry breeding probiotic strains of the genus Lactobacillus are commercially mostly used (Cisek and Binek 2014); Bacillus spp. are also frequently used (Novak et al 2011); at recent time representatives of the genus Enterococcus have also been reported especially in relation with immunological parameters (Stasova et al 2015;Karaffova et al 2017).…”
Section: Doi: 1017221/12/2017-cjasmentioning
confidence: 99%